2020
DOI: 10.1051/bioconf/20201700250
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bacterial preparations on the growth, development and quality indicators of sugar beet yield

Abstract: Experimental samples of biological products based on endophytic microorganism strains were tested on sugar beet root plants. The studies were carried out at ZAI Agrofirm LLC, Zay District, the Republic of Tatarstan. The most effective preparations applied at the early stages (3–4 leaf phase) were RECB – 31 B (1.5 l/ha), RECB – 74 B (1.5 l/ha), RECB – 74 B (1.5 l/ha), RECB – 44 B (2.0 l/ha), RECB – 50 B (2.0 l/ha), and RECB – 74 B (2.0 l/ha). Biological preparations applied in the row closing leaf phase have an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
0
7
0
2
Order By: Relevance
“…One of the main indicators of carrot quality is the carotenoid content [ 59 , 60 ]. It was shown that organic fertilizers can increase the content of nutrients such as β-carotenes [ 20 ]. Concerning the implications of microbial plant biostimulants on improving product quality, Chandrasekaran with coauthors [ 61 ] reported that the inoculation of PGPR strain, Bacillus subtilis CBR05 induced a significant increase in tomato quality in terms of carotenoids profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main indicators of carrot quality is the carotenoid content [ 59 , 60 ]. It was shown that organic fertilizers can increase the content of nutrients such as β-carotenes [ 20 ]. Concerning the implications of microbial plant biostimulants on improving product quality, Chandrasekaran with coauthors [ 61 ] reported that the inoculation of PGPR strain, Bacillus subtilis CBR05 induced a significant increase in tomato quality in terms of carotenoids profile.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies about the effects of plant probiotics on the yield of vegetables, and especially, on the content of their bioactive compounds [ 5 , 12 , 17 , 18 ]. The increase in sugar accumulation and yield was observed in sugar beet roots after treatment with microbial biostimulants [ 19 , 20 ]. Additionally, Bona with coworkers [ 21 ] revealed that inoculation with the strain Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…As the researchers note, for most biological agents of bacterial nature, optimal conditions for growth and development are possible with sufficient access to oxygen (aerobes) and moderate positive temperatures [3,4]. It is the great dependence of the effectiveness of biological protection on the influence of environmental factors that largely determine and restrains its implementation in practice [5].…”
Section: Introductionmentioning
confidence: 99%
“…Spring wheat in the phase of full sprouting does not have a powerful root system that can compete with weeds. For the accelerated development of roots, it is necessary to create optimal conditions for their growth -this is access to moisture, air, and nutrients [4][5][6]. For the same purpose, according to many researchers, is the use of growth stimulants during pre-sowing seed treatment and during vegetation [7][8][9].…”
Section: Introductionmentioning
confidence: 99%